PROCEDURAL LABOUR LAW STUDIES WITH A FOCUS ON ACTIVE LEARNING - Moya-Amador, Rosa (European Scientific Journal, ESJ, 2014)
We introduce two innovative techniques used to promote a more active approach to learning, with respect to the Procedural Labour Law course subject. On the other hand, audiovisual practical materials enabled students to be virtually present at courts and extrajudicial conflict-resolution hearings. On the other, a collective interview was used as a work-group technique, in which the students presented prepared questions to a panel of experts in labour law and social jurisdiction. The experience was continued and improved over two academic years, with very positive results for the students, promoting learning as a constructive and participatory process, and not merely a receptive one, allowing them to more easily acquire objective information and knowledge of the law and to rationalise this information from a critical standpoint through a better understanding of the underlying sociopolitical situation. The students were highly motivated, involved and collaborative, both with the teacher and with their peers, and learned to work autonomously, as the protagonists in the resolution of case studies. The approach was also highly satisfactory for the teacher, whose feeling of professional worth was enhanced through learning to teach and teaching to learn.